G "GESIH" Gerakan Sayang Ibu Hamil Dalam Upaya Pencegahan Dan Penanggulangan KEK Di Puskesmas Sungai Jingah Banjarmasin (Prosiding Seminar Nasional Masyarakat Tangguh, 2024)
Chronic Energy Deficiency (SEZ) in pregnant women can cause children born to experience cognitive decline, risk of stunting, and risk of chronic diseases in adults. The problem of pregnant women in SEZ is caused by low nutritional intake. Anemic pregnant women are at risk of giving birth to children with short birth lengths compared to mothers who are not anemic. SEZ in pregnant women can cause risks and complications including anemia, bleeding, the mother's weight does not gain normally and is exposed to infectious diseases. The SEZ of pregnant women can affect the process of fetal growth and can cause miscarriage, abortion, stillbirth, neonatal death, congenital defects, anemia in infants, intra-partum asphyxia, low birth weight (BBLR). Based on a survey conducted at the Jingah River Health Center in Banjarmasin, there were 128 cases of stanting (4.68%) and 125 pregnant women experiencing SEZ (12.4%) in 2020. These problems can be overcome by holding collaborative programs that can improve the health of pregnant women. The program can be used in overcoming problems appropriately, namely by empowering the earth through a class of pregnant women, namely GeSIH (Movement for Pregnant Women). The design in this program used is community service activities carried out in the form of education in the form of giving pocket books and conducting counseling directly during class schedules for pregnant women and pregnancy checks. The pocketbook that was created included the main page containing the identities of pregnant women and husbands, the second sheet which contained a table containing the results of the examination such as the date of the examiner, height, weight, LILA, BMI, Hb, educational information related to SEZ, nutrition during pregnancy and a checklist of food menus in a day. The conclusion of this activity is that participants who initially had a low level of knowledge of SEZ in pregnant women became more understanding about SEZ in pregnant women.